(untitled) (Modern education and development, 2025)
This article explores the multifaceted influence of emerging technologies on second language acquisition, focusing on pedagogical effectiveness, learner autonomy, and cognitive engagement. The study critically evaluates the role of artificial intelligence, mobile-assisted language learning (MALL), virtual reality (VR), and gamification in shaping modern language education. Drawing on contemporary research and theoretical frameworks including Vygotsky’s Sociocultural Theory and Mayer’s Cognitive Theory of Multimedia Learning, the paper provides a nuanced analysis of how digital environments mediate linguistic competence. The integration of adaptive learning systems and personalized feedback mechanisms is also discussed as key drivers in enhancing learner motivation and performance. The article concludes by identifying future trajectories and challenges in the digitalization of language education.